The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1111/j.1095-8649.1986.tb05192.x
|View full text |Cite
|
Sign up to set email alerts
|

The leucocytes of the elasmobranch Scyliorhinus canicula L.—a morphological study

Abstract: The leucocytes of the peripheral blood of the elasmobranch Scyliorhinus caniculu L. were examined by light, transmission and scanning electron microscopy and histochemistry. Seven distinct leucocytes were identified including lymphocytes, thrombocytes, monocytes and granulocytes. The major characteristics of these cells and their relative distribution is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…General agreement exists concerning the presence in fish of heterophilic, acidophilic and basophilic series (FEY, 1966;ZAPATA, 1979;FANGS, 1986) although more than three granulocyte types have been described (MoRRow and PULSFORD, 1980;MAIN-WARING and ROWLEY, 1985a, b;PARISH et al, 1985PARISH et al, , 1986 and one or two granulopoietic series have frequently been found (BARBER and WESTERMANN, 1981;HYDER et al, 1983;SAVAGE, 1983;HIGHTOWER et al, 1984;HoFTE et al, 1984;BAYNE, 1986).…”
Section: Discussionmentioning
confidence: 97%
“…General agreement exists concerning the presence in fish of heterophilic, acidophilic and basophilic series (FEY, 1966;ZAPATA, 1979;FANGS, 1986) although more than three granulocyte types have been described (MoRRow and PULSFORD, 1980;MAIN-WARING and ROWLEY, 1985a, b;PARISH et al, 1985PARISH et al, , 1986 and one or two granulopoietic series have frequently been found (BARBER and WESTERMANN, 1981;HYDER et al, 1983;SAVAGE, 1983;HIGHTOWER et al, 1984;HoFTE et al, 1984;BAYNE, 1986).…”
Section: Discussionmentioning
confidence: 97%
“…Increased numbers of lymphocytes in plaques suggests a cellular immune response to some antigenic component in these lesions. The structure of lymphocytes in both normal and hyperplastic epidermis was typical of fish lymphocytes (Ferguson 1976, Peleteiro & Richards 1985, Parish et al 1986, Roubal 1986, and their presence might indicate antigenic or cytocidal activity as observed towards mammalian and fish tumor cells in vitro (Evans et al 1984, Moody et al 1985, Cleland & Sonstegard 1987. While in vivo activity of lymphocytes towards fish tumor cells has not been clearly demonstrated lymphocytes do infiltrate salmon papillomas which slough off (Carlisle & Roberts 1977).…”
Section: Discussionmentioning
confidence: 92%
“…Hyperplasia in lip and body papillomas didn't attract lymphocytes, however hyperplasia can apparently be associated with increased numbers of neutrophils or macrophages (Phromsuthirak 1977). Neutrophils unusually abundant in all 3 types of papillomas possessed typical cytoplasmic organelles such as lysosomes, vacuoles and dense granules (Parish et al 1986, Roubal 1986), but cells resembling the eosinophilic granular cell widely reported in white suckers and other species (Roberts et al 1971, Barber & Westerman 1975, Lester & Daniels 1976, Roubal 1986 were not observed. Macrophages were much less prominent.…”
Section: Discussionmentioning
confidence: 96%
“…Different leukocyte (white blood cell, WBC) cell types and their structural heterogeneity between fish species imply that each fish species must be analyzed separately for its distinctive WBC traits. A number of papers give a classification of fish WBC, and the difficulties concerning exact classification and nomenclature continue today (Ellis, 1977;Hyder et al, 1983;Parish et al, 1986;Thuvander et al, 1987;Ainsworth, 1992;Hiñe, 1992;Hrubec and Smith, 2000;Kapoor and Khanna, 2004;Thrall, 2004;Thrall et al, 2004;Campbell and Ellis, 2007;Dove et al, 2010). These authors all agree that fish leukocytes are divided into granulocytes (neutrophils, eosinophils and baosphils) and agranulocytes (lymphocytes and monocytes) and their proportions vary from species to species.…”
Section: Introductionmentioning
confidence: 93%